Paradygmaty nauk społecznych a ich wykorzystanie w badaniach naukowych systemów zarządzania marketingowego - Żabiński, Leszek (Paradigms of Social Science and Their Usage in Scientific Research of Marketing Management Systems, 2006)
In the paper the author presents some tendencies in applications of social sciences basic paradigms for researching companies' marketing management systems. Research methods suggested within those paradigms come from methodology of theoretical (conceptual), empirical and formal (mathematical) research. The range of applications of those methods depends on the examined object, i.e. company management system and its marketing concept.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 17-26